ON THE HISTORY OF PUBLISHING EDUCATIONAL LITERATURE IN RUSSIA - Anna V. Zaytseva (Высшее образование в России, 2016)
The article discusses a practice of lithographing lecture notes, which was widespread in students’ community in the second half of the 19th and the early 20th century. These editions played a significant role in learning process and make a noticeable part of educational book repertory in preBrevolutionary Russia. The article focuses on students’ publishing activity in the second half of the 19th century. During this period main parts of works were formed and characteristic features of students’ publishing activity were developed. Such stages of publishing process as obtaining the professor’s consent, recording and editing of a manuscript, sending the manuscript to a lithographic workshop are examined carefully. Attention is paid for relationships between students, professors, and members of academic administration.